HIKAYAT ALFU LAILAH WA LAILAH: ANALISIS STRUKTUR NARATIF - Sangidu Sangidu (Arabic Literature Department, 2014)
The stories of the Arabian Nights were written by many people over the course of hundreds of years. The core of original stories came out of Persia and India in the earlyeighth century. They were translated into Arabic and given the name Alfu Laylah walaylah or The Thousand Nights and One Night. This set of stories was few in number andfell far short of living up to the number in its title. The Arabian Nights stand near the top of the list of literary works that haveinfluenced western literature. The first stories from the Nights to reach Europe did soaround the 12th century. Chaucer's Horse, for example, is evidently The Enchanted Horsefrom the Arabian Nights. The reaal influence began, however, Galland's translationbrought the full set of the tales to Europe in the early 1700's. The application of narrative structure to alfu lailah wa can be conducted byfocusing on the study of the plot which makes up series of events. The analysis is madeon the experiences undergone by King Syahriar and his wife, Syahrazad from thebeginning to the end of the story. The result of the analysis shows that generally the narrative structure of the storycan be divided into three parts, namely prologue, body, and epilogue. In the body of thestory, there are many stories of which narrative structures are different among them.Beside that, the Arabian Night's Entertainments stand out as one of the stellarachievements in literature. Hundreds of people contributed to their form and substancesover the hundreds of years of their development. The result has entertained andinfluenced readers for generations.